Evropska pravna država - Grabenwarter, Christoph (Pravnik, 2023)
The rule of law is not only a constitutional principle, a set of constitutional guarantees, an extension of fundamental rights and an independent judiciary. The rule of law is also part of a culture, or more precisely a specific legal culture. There may be comparable legal standards in the constitutions of other parts of the world, but just as there is a “European way of life”, there is also a “European culture of rule of law”. It is supported by the state authorities in the separation of powers of a democratic state. In individual Member States, the struggle for this culture is often arduous and fierce. A return to the roots of the European rule of law in Roman law, as well as in German-speaking Central Europe and Anglo-Saxon law, can provide a compass to help overcome the crises.
Keywords: človekove pravice; demokracija; Evropa; Evropska unija; pravna država; ustava; ustavna jamstva; vladavina prava